Analisis Strategi Fundraising Zakat pada Lembaga Amil Zakat di Kecamatan Medan Denai - Rio Dwi Maulana; Abdillah Apriansyah; Baiq Devila Hidayah; Yenni Samri Julianti Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the zakat fundraising strategies implemented by a Zakat Management Institution (Lembaga Amil Zakat) in Medan Denai District, identify the challenges encountered, and examine the efforts undertaken to increase the number of muzakki and zakat funds collected. This research employed a qualitative approach using a descriptive method. Data were collected through interviews and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the fundraising strategies applied include community outreach and education, direct engagement with prospective muzakki, collaboration with various stakeholders, and the utilization of digital media and social media platforms. The most effective methods for collecting zakat were direct approaches and social media utilization. The main challenges faced by the institution include limited public understanding of the importance of channeling zakat through authorized institutions, the persistence of direct zakat distribution practices to beneficiaries, and constraints in conducting extensive socialization programs. To maintain donors' trust, the institution emphasizes transparency and accountability in zakat fund management. Furthermore, efforts to increase the number of muzakki and zakat collections are carried out through educational programs, partnership expansion, and the optimization of digital services. The study concludes that the fundraising strategies implemented are relatively effective and have promising prospects for future development, supported by increasing public awareness and the growing use of digital technology in zakat management.